Between ketman and defense of the university profession: Mihailo Konstantinović in the academic purges during the 1940s - Popović Dejan (Anali Pravnog Fakulteta u Beogradu)
Under Communist rule in Yugoslavia a university professor could either raise his voice and pay a high price, join the Party or accept the ketman practice. Mihailo Konstantinović tried to find a fourth way: retain the office, not cross to the red side and avoid being perceived as a ketman. Konstantinović was absent at the meeting of the Faculty's Council in 1946 when Dragoljub Jovanović was expelled. When in 1947 Communist students required removal of professors Milan Vladisavljević and Đorđe Mirković, Konstantinović was one of the professors who defended them, exposed to attacks by his Communist colleagues. The Council eventually relinquished the decision to higher authorities and Vladisavljević and Mirković were consequently dismissed. The following year assistant professor Milivoje Marković was targeted but due to the Communist pressure fewer colleagues defended him. Konstantinović did not take a stand on that occasion. His most important goal was to preserve the Faculty.